Isolamento de bactérias láticas produtoras de bacteriocinas e avaliação de sua atividade frente a patógenos alimentares em sistema de bioconservação de produto lácteo - Costa, Ana Carolina Cabral Carvalhaes (2016)
Due to their antagonistic activity against undesirable microorganisms, lactic acid bacteria (LAB) are a promising alternative for conservation and improvement of food safety. The aim of this work was isolate, from fresh Minas cheese, bacteriocin producing LAB with potential for use in biopreservation systems of dairy products. For this purpose, cheese samples were evaluated at the beginning and end of their shelf life and the isolation was performed by surface plating on MRS agar. The antimicrobial activity was verified by antagonism assay using Listeria monocytogenes ATCC 7644 and Staphylococcus aureus ATCC 25923 as indicators microorganisms. The selected LAB were submitted to the spot-on-the-lawn test, Gram stain, catalase and oxidase production and glucose metabolism in Hugh & Leifson broth. The occurrence of inhibition due to the production of organic acids and bacteriophages was discarded. The protein nature of antagonistic substances was confirmed by using proteases. After the well-diffusion assay, four LAB with satisfactory antagonistic activity against the indicators microorganisms were selected for identification by sequencing of the 16S RNA gene. All bacteria were identified as Lactococcus lactis. Based on antagonism assay, Lactococcus lactis QMF 11 was selected for use in co-inoculation studies with pathogens in pasteurized milk, kept at 8°C for 10 days. Lactobacillus sakei ATCC 15521 was used as negative control for bacteriocin production. After incubation period, monocultures of Listeria monocytogenes reached 8 log cfu mL-1 and in the presence of Lactobacillus sakei ATCC its population achieved 7.3 log cfu mL-1. However, when co-inoculated with Lactococcus lactis QMF 11, Listeria monocytogenes counts were maintained at the initial inoculum levels, not surpassing 2.3 log cfu mL-1 at the end of analysis. Regarding to Staphylococcus aureus, in the end of the experiment, cultures counts were 5.4 log cfu mL-1 (monocultures), 5.0 log cfu mL-1 (co-inoculation with Lactobacillus sakei) and 4.7 log cfu mL-1 (co-inoculation with Lactococcus lactis QMF 11). Despite the lower growth inhibition in comparison with Listeria monocytogenes, Staphylococcus aureus growth was significantly affect (p < 0.005) by the presence of Lactococcus lactis QMF 11, indicating that this strain has potential for use as biopreservative culture in dairy products.